Favorable pleiotropic effects of sodium glucose cotransporter 2 inhibitors: head-to-head comparisons with dipeptidyl peptidase-4 inhibitors in type 2 diabetes patients - Shao, Shih-Chieh (Cardiovasc Diabetol, 2020)
BACKGROUND: Sodium glucose cotransporter 2 (SGLT2) inhibitors have shown greater reductions of cardiovascular event risks than dipeptidyl peptidase-4 (DPP4) inhibitors, whereby possible mechanisms may involve the better pleiotropic effects of SGLT2 inhibitors. However, no published data are currently available to directly compare glycemic and pleiotropic effects in real-world type 2 diabetes patients initiating SGLT2 inhibitors or DPP4 inhibitors. METHOD: We conducted a retrospective cohort study by analyzing the Chang Gung Research Database, the largest multi-institutional electronic medical records database in Taiwan. We included patients newly receiving SGLT2 inhibitor or DPP4 inhibitor intensification therapy for type 2 diabetes from 2016 to 2017. We matched SGLT2 inhibitor users to DPP4 inhibitor users (1:4) by propensity scores to ensure comparable characteristics between the groups. We primarily evaluated 1-year post-treatment changes of hemoglobin A1c (HbA1c) after SGLT2 inhibitor or DPP4 inhibitor initiation, using two-tailed independent t-test. We also evaluated post-treatment changes in body weight, systolic blood pressure (SBP), alanine aminotransferase (ALT) and estimated glomerular filtration rate (eGFR) values, associated with SGLT2 inhibitors and DPP4 inhibitors. RESULTS: We identified a cohort of 2028 SGLT2 inhibitors and 8112 matched DPP4 inhibitors new users. SGLT2 inhibitors and DPP4 inhibitors showed similar HbA1c reductions (− 1.0 vs. − 1.1%; P = 0.076), but patients receiving SGLT2 inhibitors had greater improvements in body weight (− 1.5 vs. − 1.0 kg; P = 0.008), SBP (− 2.5 vs. − 0.7 mmHg; P < 0.001) and ALT values (− 4.1 vs. − 0.0 U/l; P < 0.001) and smaller declines in eGFR values (− 2.0 vs. − 3.5 ml/min/1.73 m(2); P < 0.001) when compared to DPP4 inhibitors. CONCLUSION: SGLT2 inhibitors had glucose-lowering effects comparable to those of DPP4 inhibitors but more favorable pleiotropic effects on body weight, ALT and eGFR changes, potentially improving type 2 diabetes patients’ cardio-metabolic disease risks.